Towards a 100% hydrogen domestic gas network: Regulatory and commercial barriers to the first demonstrator project in the United Kingdom. (30th June 2022) - Smith, Connor; Mouli-Castillo, Julien; van der Horst, Dan; Haszeldine, Stuart; Lane, Matthew
Abstract: In the debate on the decarbonisation of heat, renewable electricity tends to play a much more dominant role than green gases, despite the potential advantages of gas in terms of utilising existing transportation networks and end-use appliances. Informed comparisons are hampered by information asymmetry; the renewable electricity has seen a huge grid level deployment whereas low-carbon hydrogen or bio-methane have been limited to some small, stand-alone trials. This paper explores the regulatory and commercial challenges of implementing the first UK neighbourhood level 100% low-carbon hydrogen demonstration project. We draw on existing literature and action research to identify the key practical barriers currently hindering the ability of strategically important actors to accelerate the substitution of natural gas with low carbon hydrogen in local gas networks. This paper adds much needed contextual depth to existing generic and theoretical understandings of low-carbon hydrogen for heat transition feasibility. The learnings from pilot projects, about the exclusion of hydrogen calorific value from the Local Distribution Zone calorific value calculation, Special Purpose Vehicle companies, holding of liability and future costs to consumers, need to be quickly transferred into resilient operational practice, or gas repurposing projects will continue to be less desirable than electrification using existing regulations, and with more rapid delivery. Highlights: This paper explores barriers for the first UK 100% hydrogen distribution project. Learnings from pilot projects need to be transferred into UK operational practice. Existing regulations present barriers to gas distribution innovation projects.